2013
DOI: 10.1590/s0102-86502013001100005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of presynaptic and postsynaptic action of local anesthetics in rats

Abstract: PURPOSE:To assess the probable actions of ropivacaine, 50% enantiomeric excess bupivacaine mixture (S75-R25) and levobupivacaine on neuromuscular transmission in vitro. METHODS:Thirty rats were distributed into groups (n=5) according to the drug used: ropivacaine, bupivacaine (S75-R25) and levobupivacaine. The concentration used for the three local anesthetics (LA) was 5 µg.mL.-1 The following parameters were evaluated:1) LA effects on membrane potential (MP) and miniature end plate potential (MEPP). A chick b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
0
6
0
5
Order By: Relevance
“…In the postsynaptic region, local anesthetics lead to receptor desensitization, cause temporary occlusion of nicotinic receptor channels, and interfere in the process of excitation–contraction coupling of the muscle fiber. [42,43,4649] Previous authors have found that neuraxial blockade can be related to reduction on the needed dose of NMB during GA or delayed recovery to TOF ratio of 0.9 when unchanged doses of NMB are administered. [45,47] These reports were prospective studies with smaller group of patients and with the aid of neuromuscular monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In the postsynaptic region, local anesthetics lead to receptor desensitization, cause temporary occlusion of nicotinic receptor channels, and interfere in the process of excitation–contraction coupling of the muscle fiber. [42,43,4649] Previous authors have found that neuraxial blockade can be related to reduction on the needed dose of NMB during GA or delayed recovery to TOF ratio of 0.9 when unchanged doses of NMB are administered. [45,47] These reports were prospective studies with smaller group of patients and with the aid of neuromuscular monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Presynaptic and postsynaptic events have been described [1][2][3][4]9,10 . To identify the probable mechanism of interaction and potentiation of the block produced by pancuronium, in a preparation previously exposed to levobupivacaine, electrophysiological studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of bioelectrical potentials, it was observed that levobupivacaine, in the concentration employed, did not alter the membrane potential of muscle fibers, which remained within normal limits (-85 mV). It was demonstrated that the drug has no depolarizing action on skeletal muscle fibers, although it prevents the conduction of action potentials 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations